America's Gilded Age : an eyewitness history - Clark, Judith Freeman (New York : Facts on File, 1992)
Traces the history of the United States from 1865 to 1901 through such primary sources as memoirs, diaries, letters, contemporary journalism, and official documents
Includes bibliographical references (p. 263-266) and index
Keywords: United States -- History -- 1865-1921 -- Sources; United States -- History -- 1865-1921 -- Sources